2006
DOI: 10.1002/jbm.a.30931
|View full text |Cite
|
Sign up to set email alerts
|

Markedly different effects of hyaluronic acid and chondroitin sulfate‐A on the differentiation of human articular chondrocytes in micromass and 3‐D honeycomb rotation cultures

Abstract: A source of morphologically and functionally available human cartilagenous tissue for implantation is required in the field of tissue engineering. To achieve this goal, we evaluated the effects of hyaluronic acid (HA-810 and 1680 kDa), and chondroitin sulfate (CS-A 16 and C-34 kDa) on human articular chondrocytes (HC) in micromass and rotation culture conditions. Cell proliferation was increased by CS-A 16 kDa under micromass and rotation cultures, while cell differentiation was increased under rotation but no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…1,[4][5][6][7][8][9][10][11][12][13][14][15]17,27,28,30,31 Collagen I production was generally broad-ranged in all biomaterial encapsulated chondrocytes, which might be due to the ubiquitous stimulative properties of TGF-b that was used as an ingredient for the cell culture medium used in our study. 32 Besides certain outliers, a trend towards higher Collagen I expression in alginate-fibrin encapsulated chondrocytes could be observed, whereas Collagen I expression was constantly low in pellet-cultured cells.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…1,[4][5][6][7][8][9][10][11][12][13][14][15]17,27,28,30,31 Collagen I production was generally broad-ranged in all biomaterial encapsulated chondrocytes, which might be due to the ubiquitous stimulative properties of TGF-b that was used as an ingredient for the cell culture medium used in our study. 32 Besides certain outliers, a trend towards higher Collagen I expression in alginate-fibrin encapsulated chondrocytes could be observed, whereas Collagen I expression was constantly low in pellet-cultured cells.…”
Section: Discussionmentioning
confidence: 95%
“…It is known that biomaterial-free pellet culture can elicit profound chondrogenic effects upon dedifferentiated chondrocytes or mesenchymal stem cells. [13][14][15]17,18,[27][28][29] A major drawback of those techniques is the large amount of cells that is needed to generate sufficiently sized cartilage constructs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies previously carried out 5 on cartilage regeneration have shown that GAGs are fundamental for presenting motifs for cell attachment and migration. In addition, GAGs have also been attributed to activating pathways that govern proliferation and differentiation as well as assembly of the ECM (Pieper et al, 2000, Banu and Tsuchiya, 2007, Wu et al, 2010, Correia et al, 2011. Specifically, chondroitin sulphate (CS) which is the main type of GAG in cartilage ECM has been shown to stimulate chondrogenesis in vitro and promotes cellular ingrowth and cartilaginous tissue formation in vivo (van Susante et al, 2001, Buma et al, 2003.…”
Section: Introductionmentioning
confidence: 99%
“…There have been a number of papers published on the subject of crosslinking GAGs for biomedical use [2634]. A good example of this approach is given by the work of Li et al [29].…”
Section: Introductionmentioning
confidence: 99%